If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + 9 + -3y = 2y + 4 Reorder the terms: 9 + 9y + -3y = 2y + 4 Combine like terms: 9y + -3y = 6y 9 + 6y = 2y + 4 Reorder the terms: 9 + 6y = 4 + 2y Solving 9 + 6y = 4 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 9 + 6y + -2y = 4 + 2y + -2y Combine like terms: 6y + -2y = 4y 9 + 4y = 4 + 2y + -2y Combine like terms: 2y + -2y = 0 9 + 4y = 4 + 0 9 + 4y = 4 Add '-9' to each side of the equation. 9 + -9 + 4y = 4 + -9 Combine like terms: 9 + -9 = 0 0 + 4y = 4 + -9 4y = 4 + -9 Combine like terms: 4 + -9 = -5 4y = -5 Divide each side by '4'. y = -1.25 Simplifying y = -1.25
| 8(4y-5)=3y+5y | | [-6+(-13)]+8=-6+(m+8) | | 11-4p=-5(p-1) | | -8a-2(2a-1)=-40+2a | | 3.2+0.17-w=5.75 | | 5v+18=2(8v-2) | | 92+2x=78+3x | | 86=32+6(x-2) | | 25+2m=5(m+2) | | -10+r=-7(6+r) | | 8y-16=13y-9 | | -6+4(1+8x)=-194 | | 188=-4(1+6b) | | 7-6(-5b-5)=157 | | 9-2(-5x+8)ifx=-9 | | 7-66(-5b-5)=157 | | -6+5x=9 | | X-9=3.5 | | -3(6k-5)=123 | | f(x)=3-2(1) | | -4(-7n+8)=-228 | | b^2+11b=-30 | | 4x-x=-5+8x | | x^2=-99 | | -4r+5=10-5r | | -7b-2b=8-8b | | 9=3x-6 | | f(x)=3-2(0) | | 6+3x-x=x+2 | | X-7325=4561 | | 19.2+(-7+3.8)= | | 150=3x |